Pentingnya Peran Orang Tua Dalam Membentuk Identitas Gender - Kurnia Sary; Rani Maulidina; Riska Yuniar; Suci Utami Putri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Understanding gender has great significance for various levels of society, including children, adolescents and adults. Gender identity refers to the term used to describe an individual's tendencies regarding female and male roles. This research aims to explore information about the importance of the role of parents in the formation of gender behavior through a literature review from various sources. The qualitative descriptive method in this article uses a type of research in the form of library research (literature review), specifically collecting information or scientific articles related to literature reviews of a library nature. From the previous evaluation, it can be concluded that the care provided by parents has a significant impact in forming gender identity in young children.